REVIEW of the book “Western Caspian region as part of the Russian Empire (1722-1735): Collection of archival documents” (Makhachkala: Mavraev, 2020) - Gezalova, Nigar Rovsan gyzy (History, Archeology and Ethnography of the Caucasus, 2022)
The most important factor in the development of Caucasian studies is the expanding of the source base through the use of archival material, the development of methods of analysis and its processing. Today, the careful and detailed study of new archival documents helps to make corrections and sheds light on a number of questions about the history of the region that have been overlooked by researchers. In this connection, the materials collected from the archives of the Russian State Archive of Ancient Acts, the Russian State Military Historical Archive, and the Central State Archive of the Republic of Dagestan are of great interest when studying the political, social and economic situation in the region in the beginning of the 18th century. The collection under review is a major contribution to the development of historiography of imperial Russian policy in the Caucasus in 1722-1735 and makes it possible to widen the scope of research issues. With the help of new approaches and new sources, which are being researched for the first time, the materials of this collection allow a new reconstruction of the Russian imperial policy in the Caspian region. This book is a major contribution to the development of historiography of Russian imperial policy in the Caucasus between 1722 and 1735 and allows us to extend the scope of our research.
Keywords: source study; archival documents; Russian Empire; Dagestan; Azerbaijan; Northern Iran; review